The ropemaker - Dickinson, Peter, 1927-2015. (New York : Delacorte Press, 2001)
When the magic that protects their Valley starts to fail, Tilja and her companions journey into the evil Empire to find the ancient magician Faheel, who originally cast those spells.
Mode of access: Internet.